The value of a loss: The impact of restricting tax loss transfers - Anna Theresa Bührle; Elisa Casi-Eberhard; Barbara Stage; Johannes Voget (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
We study the economic consequences of anti-loss trafficking rules, which disallow the use of loss carry-forwards as tax shield after a substantial ownership change. Using staggered changes to these rules, we find that limiting the transfer of tax losses reduces the number of M&As with loss-making targets by 22%. We further observe decreases in birth and survival rates of young companies in response to stricter regulations and vice versa. Tightening (loosening) anti-loss trafficking rules impairs (increases) return on assets, especially for R&D-intensive firms, and stricter rules lead to a decrease in successful patent applications.
Keywords: G34; G38; H25; 330; Mergers and acquisitions; anti-loss trafficking rules; taxes; market entry; market exit; productivity; innovation